Investigation of throughput and packet drop for Hata model on VANET using NCTUns simulation software for open area and suburban area / Rosmawani Samsudin - Samsudin, Rosmawani (2012)
Vehicular Ad-hoc Network (VANET) is a special case of MANET. Their resemblance is the rapidly moving car as nodes and incessantly changing network topologies. The purpose of this project is to run VANET using National Chiao Tung University network simulator (NCTUns). Simulation is the research tools of choice to obtain throughput and packet dropped at each node at different speed. Simulation will be accomplish the modification by investigating the variation in vehicular mobility model between the measured and predict values, according to the Hata propagation model for open area and suburban area. The investigation was done from 5 to up 20 V ANET nodes. The algorithms considered are Ad-hoc On-demand Distance Vector (AODV) protocol. The performance measurements are based on the various parameters of in-out throughput and number of packet dropped.